CRISPR library designer (CLD): software for multispecies design of single guide RNA libraries - Heigwer, Florian; Zhan, Tianzuo; Breinig, Marco; Brügemann, Dirk; Boutros, Michael (Genome biology, 2016)
Background: Genetic screens using CRISPR/Cas9 are a powerful method for the functional analysis of genomes. Results: Here we describe CRISPR library designer (CLD), an integrated bioinformatics application for the design of custom single guide RNA (sgRNA) libraries for all organisms with annotated genomes. CLD is suitable for the design of libraries using modified CRISPR enzymes and targeting non-coding regions. To demonstrate its utility, we perform a pooled screen for modulators of the TNF-related apoptosis inducing ligand (TRAIL) pathway using a custom library of 12,471 sgRNAs. Conclusion: CLD predicts a high fraction of functional sgRNAs and is publicly available at https://github.com/boutroslab/cld.